2021
DOI: 10.3390/jcm10143167
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers in Differential Diagnosis of Idiopathic Pulmonary Fibrosis and Connective Tissue Disease-Associated Interstitial Lung Disease

Abstract: Introduction: The goal of this study is to determine whether Advanced glycosylated end-products (AGE), Advanced oxidation protein products (AOPP) and Matrix metalloproteinase 7 (MMP7) could be used as differential biomarkers for idiopathic pulmonary fibrosis (IPF) and connective tissue disease-associated interstitial lung disease (CTD-ILD). Method: Seventy-three patients were enrolled: 29 with IPF, 14 with CTD-ILD, and 30 healthy controls. The study included a single visit by participants. A blood sample was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Since the accurate diagnosis of ILD implies different therapeutic strategies influencing the management of these patients [ 1 , 2 , 3 , 34 ], the identification of biomarkers for the differential diagnosis between IPF and other ILD is relevant. In this regard, previous studies from our group and others have revealed the potential relevance of biomarkers such as endothelial progenitor cells and advanced glycosylated end-products to discriminate between IPF and ILD associated with connective tissue diseases [ 26 , 35 ]. In a similar manner, the glycoprotein gremlin-1 has been proposed for the differential diagnosis of IPF compared to non-IPF ILD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the accurate diagnosis of ILD implies different therapeutic strategies influencing the management of these patients [ 1 , 2 , 3 , 34 ], the identification of biomarkers for the differential diagnosis between IPF and other ILD is relevant. In this regard, previous studies from our group and others have revealed the potential relevance of biomarkers such as endothelial progenitor cells and advanced glycosylated end-products to discriminate between IPF and ILD associated with connective tissue diseases [ 26 , 35 ]. In a similar manner, the glycoprotein gremlin-1 has been proposed for the differential diagnosis of IPF compared to non-IPF ILD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of UIP is a marker of poor prognosis no matter the specific ILD diagnosis [ 39 ], and elevated MMP7 levels are not specific to IPF [ 40 ]. Aberrant MMP7 expression may be a common feature of end-stage fibrotic disease, and mechanisms relating to its regulation and particularly its activation in the fibrotic epithelium should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-7 enhances neutrophil influx to damage AECs, which promotes the development of fibrosis, and then reverses the fibrotic situation by attracting immunosuppressive leukocytes. Many studies have identified MMP-7 as a potential diagnostic and prognostic biomarker for IPF [136][137][138]. Multiple bioinformatic methods have demonstrated that mmp7 gene is significantly correlated with the prognosis and occurrence of IPF.…”
Section: Mmp-7mentioning
confidence: 99%